A static MEH handover scheme based on load balancing - Haipeng LIU (Dianxin kexue)
Based on the MEH (mobile edge host) handover scheme proposed by ETSI (European Telecommunications Standards Institute),an improved and supplementary static handover scheme was put forward.By transferring the former C-MEH (controlling MEH) to a neighbor server with lighter load,the scheme decreased the average waiting time of a signal message at the former C-MEH site.The negative effect of bottle-neck at the former C-MEH could also be lightened.Analysis and simulation results show that the scheme can provide effective and positive supplementary to the ETSI specification in balancing network load and improving user’s satisfaction.